New mixture distribution of Garima and Lindley - Karakas, Ayse Metin; Demir, Aslihan; Dogan, Mine; Calik, Sinan (Taylor & Francis Ltd, 2022)
The Garima and Lindley distributions are important and widely used distributions for the distribution of lifespan as well as the distribution of wealth The Garima distribution is mainly used to express the new life distribution, the Lindley distribution is a way of describing the life of a life or tool. it can be used in a wide variety of fields, ranging from biology, engineering and medicine. In this article, the usual properties of the Garima-Lindley distribution mixture were obtained. Cumulative distribution function, risk rate, shortness rate, inverse risk function, odd function and cumulative risk function, moment r, characteristic function of the generator function of moment, moments, mean and variance, Bonferoni and Lorenz curve, order statistics, NILE, mean time between shortness (MTBF) and stress-resistance reliability were also obtained. Graphics and some results were obtained with the help of MATLAB\R2018a and Wolfram Mathematica 7 programs.
Keywords: Garima distribution; Lindley distribution; Cumulative distribution function; Characteristic function; Order statistics